Shelter in Place - Roberts, Nora; Roberts, Nora (Brilliance Audio, 2018)
From number one New York Times best selling author Nora Roberts comes a powerful tale of heart, heroism, and propulsive suspense.
Keywords: Mass shootings -- Fiction; Massacre survivors -- Fiction; Shopping malls -- Maine; Fiction; Portland (Me.) -- Fiction; Psychological fiction; Thrillers (Fiction); Audiobooks